2019
DOI: 10.1155/2019/8306492
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Proton Radiation Influence on the Performance of a Polycrystalline Silicon Solar Cell

Abstract: The aim of this work is to study the behaviour of a silicon solar cell under the irradiation of different fluences of high-energy proton radiation (10 MeV) and under constant multispectral illumination. Many theoretical et experimental studies of the effect of irradiation (proton, gamma, electron, etc.) on solar cells have been carried out. These studies point out the effect of irradiation on the behaviour of the solar cell electrical parameters but do not explain the causes of these effects. In our study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, we can conclude that taking into account change in the wide of the SCR doesn't affect the conversion efficiency and that it is removal of majority charged carriers (Rc changes) which is responsible of the type-conversion of the base. Of course, the previous studies taking into account only change in diffusion length don't exhibit type conversion [15,16,17].…”
Section: Figure 4: Open Circuit Voltage Versus Fluencesmentioning
confidence: 94%
“…Thus, we can conclude that taking into account change in the wide of the SCR doesn't affect the conversion efficiency and that it is removal of majority charged carriers (Rc changes) which is responsible of the type-conversion of the base. Of course, the previous studies taking into account only change in diffusion length don't exhibit type conversion [15,16,17].…”
Section: Figure 4: Open Circuit Voltage Versus Fluencesmentioning
confidence: 94%
“…Other authors are interested in the effect of light intensity on the performance of PV cells and observed that increasing the intensity of incident light improves performance of PV cell [2] [4]. In addition, studies on the effect of an external magnetic field [5] [6] and of a protons irradiation on the performance of PV cells [7] have been made and it appears that the Magnetic fields as well as protons degrade performances of PV cells. The multiplicity of sources of electromagnetic fields (development of telecommunication systems) and the operating conditions of PV cells under concentration of light (high temperatures)…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of studies of the effects of ionizing radiation on the properties of semiconductor materials and devices is increasing due to the increasing use of these processes in industrial technologies un-der controlled exposure, as well as the use of devices under uncontrolled environmental exposure [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%